Programas de luz para codornas de corte criadas em região equatorial - Aguiar, Germana Costa (2016)
Two experiments were carried out to evaluate the effect of light programs for quails (Coturnix coturnix) grown in equatorial region on performance and carcass characteristics at different slaughter ages, sexual maturity, performance and quality of eggs during the laying period. In the first experiment, 1500 sex quails were distributed in a completely randomized design according to a 2x3 factorial scheme, with two sexes (males and females) and three light programs, with five replicates of 50 birds. The light programs were applied in the period from 7 to 49 days old, being natural the natural light program consisting of 12 hours and 30 minutes of natural light and 11 hours and 30 minutes without artificial lighting during the night. The intermittent lighting program, consisting of 18 hours of light and 6 hours of darkness, the period of light composed of 12 hours and 30 minutes of natural light and 5 hours and 30 minutes of artificial light interspersed by periods of darkness (1 hour and 23 minutes of light and 1 hour and 23 minutes of dark) and the continuous light program the birds were subjected to 23 hours of constant light, being 12 hours and 30 minutes of natural light, 10 hours and 30 minutes of artificial light and 1 hour of dark. During the whole experimental period, the birds of the different treatments were submitted to the same feeding program. For the ration consumption, in all periods, there was no effect of the interaction (light x sex), however, the natural light program resulted in lower consumption in relation to intermittent and continuous illumination, which did not differ from each other. Although females showed higher consumption, there was a significant difference only in the periods of 7 to 42 days and 7 to 49 days. For weight gain, there was interaction effect (light x sex) in periods of 7 to 42 days and 7 to 49 days. While weight gain among males did not differ significantly, the natural light program resulted in lighter females relative to intermittent and continuous lighting, which didn’t differ from each other. Females were heavier than males, in all light programs and breeding seasons. The feed conversion was not influenced by the interaction (light x sex) in all periods and wasn’t influenced by the factors isolated in the period from 7 to 35 days old. However, in the periods from 7 to 42 days and from 7 to 49 days, the natural light program resulted in a better result in relation to the intermittent and continuous lighting, which did not differ between them, and the females showed better feed conversion. For the characteristics of carcass and viscera, there was interaction effect (light x sex) only for carcass and chest in the period from 7 to 49 days. Carcass yield among males did not differ significantly; For females, the natural light program resulted in higher yields relative to intermittent and continuous lighting, which did not differ from each other. Thus, the males submitted to intermittent and continuous illumination presented higher carcass yield in relation to females. For chest yield, there was no difference between females, whereas for males, the natural light program resulted in higher yield in relation to intermittent and continuous lighting, which did not differ from each other. Thus, males submitted to intermittent and continuous illumination had lower breast yield in relation to females. The thigh + drumstick yield was not influenced by the factors studied, while the proportion of abdominal fat was lower for birds subjected to natural light and was higher in females at 49 days old. The proportion of liver at 35 days old was not influenced by the factors studied, however, it was lower for birds subjected to natural light and for males at 42 and 49 days old. In the second experiment, it were used 240 females quails remaining from the first experiment. The birds were transferred to a production shed, according to a completely randomized experimental design, with three treatments and five replicates of 16 birds. The experimental period was divided into four periods of 21 days, during which the birds of all treatments were submitted to the same light and feeding program. For the statistical analysis of the production data and egg quality, besides the effect of the light programs of the growth phase, the effect of the posture cycle period was added to the model. The birds that in the growth phase were submitted to the continuous or intermittent light program were more precocious when compared to those that were submitted to the natural light program. For performance variables, except egg weight, there was interaction effect (light program x posture cycle period), however, this effect was not observed for egg quality variables. The birds submitted to the natural light program in the growth phase showed lower ration intake until the second period (71 to 92 days old), lower egg production during all periods, lower egg mass and worse feed conversion until the third period (93 to 114 days old). These variables did not differ between the continuous and the intermittent program from the second period (71 to 92 days old). Light programs in growth stage didn’t influence the quality characteristics of the eggs, however, as the age of the birds increased, there was egg yolk reduction and egg shell ad albumen increase, from the first (49 to 71 days old) for the remaining periods of the cycle, and worsening of albumen and shell quality, from the first (49 to 71 days old) to the third period (93 to 114 days old). It is concluded that in equatorial region it is possible to use a light program with only natural light for the creation of male and female quails intended for meat production from 7 to 49 days old. However, the natural lighting program increases the age of sexual maturity and worsens the performance of birds during the production cycle (49 to 136 days old). The intermittent lighting program maintains the sexual maturity, performance and egg quality during the production cycle.